Sport Concussion Assessment Tool: baseline and clinical reference limits for concussion diagnosis and management in elite Rugby Union. Issue 2 (February 2021) - Tucker, R.; Falvey, E.C.; Fuller, Gordon W.; Hislop, M.D.; Patricios, J.; Raftery, M.
Abstract: Objectives: Rugby Union has adapted the Sports Concussion Assessment Tool (SCAT) into an abridged off-field concussion screen and the complete SCAT is used during diagnostic screens performed after head impact events. No firm guidelines exist as to what should be considered "abnormal" and warrant further evaluation. This study evaluates SCAT performances in 13, 479 baseline SCAT assessments, and proposes clear reference limits for each sub-component of the SCAT5. Baseline reference limits are proposed to guide management of baseline testing by identifying abnormal sub-tests, enhancing the clinical validity of baseline screens, while clinical reference limits are identified to support concussion diagnosis when no baseline is available. Design: Cross sectional census sample. Methods: 13, 479 baseline SCATs from 7565 elite male rugby players were evaluated. Baseline reference limits were identified for each sub-test as the sub-test result achieved by approximately 5% of the population, while clinical references limits corresponded to the sub-test score achieved by as close as possible to 50% of the cohort. Results: Players reported symptoms 35% (95% CI 1.29–1.42) more frequently during SCAT5 than SCAT3 baseline assessments (mean 1.4 ± 2.7 vs 1.0 ± 2.4). Ceiling effects were identified for many cognitive sub-tests within the SCAT. Baseline and Clinical reference limits corresponding to the worst performing 5th percentile and 50th percentile were described. Conclusions: Targeted baseline re-testing should be repeated when abnormal sub-tests are identified according to proposed baseline reference limits, while a more conservative clinical reference limit supports concussion diagnosis during screens in diagnostic settings.